2013
DOI: 10.1021/ef401787q
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Fuel Pretreatment: Simultaneous Torrefaction and Grinding of Biomass

Abstract: Combining torrefaction and grinding of biomass in one reactor may be an attractive fuel pretreatment process. A combined laboratory torrefaction and ball mill reactor has been constructed for studies of the influence of temperature and residence time on the product yields and particle size reductions of Danish wheat straw, spruce chips, and pine chips. On the basis of initial experiments, which evaluated the influence of reactor mass loading, gas flow, and grinding ball size and material, a standard experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Various authors have found a similar trend with woody as well as herbaceous biomass (Deng et al 2009;Chen et al 2011a, b;Chew and Doshi 2011;van der Stelt et al 2011;Wang et al 2011;Agar and Wihersaari 2012;Shang et al 2012;Lu and Chen 2013;Ohliger et al 2013;Saleh et al 2013;Satpathy et al 2014;Mei et al 2015). However increasing the severity (temperature and time) also translates to more energy use for pretreatment, therefore an optimum level of severity should be developed and this is likely to depend on the type of biomass.…”
Section: Grindabilitymentioning
confidence: 79%
“…Various authors have found a similar trend with woody as well as herbaceous biomass (Deng et al 2009;Chen et al 2011a, b;Chew and Doshi 2011;van der Stelt et al 2011;Wang et al 2011;Agar and Wihersaari 2012;Shang et al 2012;Lu and Chen 2013;Ohliger et al 2013;Saleh et al 2013;Satpathy et al 2014;Mei et al 2015). However increasing the severity (temperature and time) also translates to more energy use for pretreatment, therefore an optimum level of severity should be developed and this is likely to depend on the type of biomass.…”
Section: Grindabilitymentioning
confidence: 79%
“…Torrefaction [38,39] It is a process of slow heating of biomass residues materials to a temperature of near about 300 0 C. Due to this, volatile materials and smoke evolving products are reduces to make final product better.…”
Section: Pre-treatment Methods Of Solid Biomass Fuelsmentioning
confidence: 99%
“…Grinding [39] It is a process of grinding of the biomass raw/residues material at specific size depends upon the densification technology selected.…”
Section: Pre-treatment Methods Of Solid Biomass Fuelsmentioning
confidence: 99%
“…Ibrahim et al found that increasing the severity of the thermal treatment improves the grindability of both softwoods and hardwoods (Ibrahim et al 2013) while Bridgeman et al found that the higher temperature severity caused torrefied Miscanthus and Willow to exhibit similar grindability as coal (Bridgeman et al 2010). Various authors have found a similar trend with woody as well as herbaceous biomass (Deng et al 2009;Chen et al 2011a, b;Chew and Doshi 2011;van der Stelt et al 2011;Wang et al 2011;Agar and Wihersaari 2012;Kim et al 2012;Shang et al 2012;Lu and Chen 2013;Ohliger et al 2013;Saleh et al 2013;Satpathy et al 2014;Mei et al 2015). However increasing the severity (temperature and time) also translates to more energy use for pretreatment, therefore an optimum level of severity should be developed and this is likely to depend on the type of biomass.…”
Section: Grindabilitymentioning
confidence: 98%